Cross-layer wireless resource allocation. - Berry, R.A (IEEE Signal processing magazine)
A fundamental problem in networking is the allocation of limited resources among the users of the network. In a traditional layered network architecture, the resource to be allocated at the medium access control (MAC) and network layers utilizes communication links, viewed as "bit pipes" that deliver data at a fixed rate with occasional random errors. Though this separation has many advantages, there is a growing awareness that this simple bit-pipe view is inadequate, particularly in the context of modern wireless data networks. In this article, several basic cross-layer resource allocation problems for wireless fading channels are considered. The article focuses on the characterization of fundamental performance limits while taking into account both network layer QoS and physical layer performance.